COMPOSITIONAL CHARACTERISTICS OF ESSENTIAL OILS OF WILD POPULATIONS OF HYPERICUM PERFORATUM (ST. JOHN’S WORT) FROM LITHUANIA AND FRANCE - Judzentiene, A.; Budiene, J.; Laffont-Schwob, I.; Bessière, Jean-Marie (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Hypericum is a genus of many species that occurs in all temperate parts of the world. Five species of the genus grow wild in Lithuania whereas twenty-eight species of the same genus occur in France. H. perforatum is the most abundant and frequently used as a medical plant and is very significant in pharmacology. Many studies confirmed its antidepressant, antimicrobial, antiviral, anticancer and other activities. Numerous classes of bioactive chemical constituents have been investigated in St. John’s wort, but number of studies on volatile oils is limited. The aim of this study was to evaluate characteristics of volatile oils in various wild populations of H. perforatum from Lithuania and France.Essential oil qualitative and quantitative analyses were performed on aerial parts of H. perforatum collected in different places from Lithuania (2002-2007) and France (2000-2003). The oils were analysed by gas chromatography (FID and capillary columns HP-FFAP and CP Sil) and gas chromatography-mass spectrometry GC-MS (nonpolar cap. column DB-5). Qualitative analysis was based on a comparison of retention times, indices and mass spectra with the corresponding data in the literature and computer mass spectra libraries.A great variability was pointed out between the compositions of the essential oils from the various localities of collection. Even if trans-caryophyllene and its oxide, germacrene D, spathulenol and several aliphatic compounds were the major compounds in all the oils, those from Lithuanian plants were rich in -pinene, while this compound was almost not present in the oils from France.Acknowledgements: Lithuanian Science and Studies Foundation, project “BIOMARKS” (V-08/2008, reg. No. V-08033) in the programme “Gilibert”.